Quantitative ABCD Analysis of Integrating Corporate Social Responsibilities with Green Banking Practices by Banks from Customers’ Attraction and Retention Perspectives in Selected Indian Banks - G. Nandini Prabhu (International Journal of Case Studies in Business, IT and Education (IJCSBE), 2023)
Purpose: The ABCD (Advantages, Benefits, Constraints, and Disadvantages) analysis framework evaluates a notion or idea’s applicability in a certain circumstance. It examines the effectiveness of a concept or strategy as well as the qualities of the individual, the system, and the environment. It was also investigated for any characteristics that might be relevant to the constitution. Each component of the major characteristic of CSR activities and green banking services and its impact on attracting and retention of customers is given an appropriate score or weighting in the quantitative analysis utilizing ABCD analysis. Design: The ABCD analytical framework determines the proper score weighting that is assigned to all the significant constituents under each variable by analysing empirical data, the efficacy of CSR activities and green banking services to retain customers. The results of a focus group evaluation are then used to calculate each construct’s overall score. Findings: Using the ABCD analysis framework, a business model, concept, product, strategy, or system is examined and assessed. This method of analysis is widely used by academics in a wide range of disciplines. According to a quantitative ABCD study, the benefits factors have a substantial influence on the success of CSR and green banking services. The ABCD study supports the notion or belief that CSR inbound activities to promote green banking practises. Originality/Value: Before discussing what is being done regarding determinant issues, key attributes, factor analysis, and elementary analysis based on crucial constituent elements of CSR activities and green banking practises to retain customers, this paper begins by reviewing prior research using the ABCD analysis framework. Paper Type: Empirical analysis.